Radiation resistance of additively manufactured CrMoTaTiV compositionally complex alloys with enhanced mechanical properties - E. Aydogan; O. U. Tukac; A. Ozalp; O. El-Atwani; M. R. Chancey; H. Kim; Y. Q. Wang; B. T. Camic; S. Ozturk (Scientific Reports, 2026)
Abstract In this study, a novel Cr 10 Mo 25 Ta 25 Ti 15 V 25 refractory compositionally complex alloy (RCCA) was fabricated via laser powder directed energy deposition and subjected to irradiation at doses of up to 18 dpa at room temperature (RT) and 650 °C. Microstructural analysis revealed a dendritic BCC matrix, featuring localized enrichment of Cr, V, and Ti in the interdendritic regions, alongside a secondary FCC phase rich in Ti and O. Both compressive strength and ductility are much improved compared to the alloys produced by conventional production methods. Even at 1000 °C, the yield strength of 953 ± 70 MPa with extensive compressive ductility has been observed. Irradiation studies demonstrated that both phases remained stable, with no void formation or phase transformation. The lattice parameters of BCC matrix and FCC second phase fluctuate which was mainly attributed to local variation in composition. Loop size and density followed distinct temperature-dependent trends. At RT, limited kinetics favored loop nucleation while at 650 °C, loop coalescence was dominant. The high dislocation density inherent to additive manufacturing and sluggish diffusion in the RCCA matrix, coupled with O-rich FCC particles, contributed to the alloy’s robust radiation tolerance. These findings showcase the potential of additively manufactured RCCAs for next-generation nuclear fission and fusion applications.